2020
DOI: 10.3390/nu12092693
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Nutrients in Gastrointestinal Chronic Diseases

Abstract: Diet and nutrition are known to play key roles in many chronic gastrointestinal diseases, regarding both pathogenesis and therapeutic possibilities. A strong correlation between symptomatology, disease activity and eating habits has been observed in many common diseases, both organic and functional, such as inflammatory bowel disease and irritable bowel syndrome. New different dietary approaches have been evaluated in order improve patients’ symptoms, modulating the type of sugars ingested, the daily amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 154 publications
0
29
0
1
Order By: Relevance
“…Complementary and alternative treatments have been reported as beneficial in treating FD symptoms [ 27 ], and may thereby enhance the effectiveness of dietary management strategies. Four trials have reported that supplements containing peppermint and caraway oil were more effective than placebo in improving dyspeptic symptoms, with an average decreased intensity of epigastric pain compared to placebo [ 4 , 111 , 112 , 113 ].…”
Section: Complementary Therapies and Micronutrient Supplementation In Dietary Management Of Fdmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary and alternative treatments have been reported as beneficial in treating FD symptoms [ 27 ], and may thereby enhance the effectiveness of dietary management strategies. Four trials have reported that supplements containing peppermint and caraway oil were more effective than placebo in improving dyspeptic symptoms, with an average decreased intensity of epigastric pain compared to placebo [ 4 , 111 , 112 , 113 ].…”
Section: Complementary Therapies and Micronutrient Supplementation In Dietary Management Of Fdmentioning
confidence: 99%
“…FD is a disorder of symptoms and subtle immune changes, so the overarching goal of dietetic management is to complement medical therapy by using dietary modification to alleviate symptoms. Currently, guidance for dietetic management of FD is limited to a focus on frequent small meals, and possible trialing of reduced dietary fat intake to ameliorate slow gastric motility [ 27 ]. Due to the multifaceted nature of FD and broad range of presentation scenarios for people seeking dietary management advice for the condition, we believe that a differential dietary management approach for FD is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The Crohn’s Disease Exclusion Diet (CDED) is a validated dietary intervention, firstly conceived in 2014 by Sigall-Boneh and colleagues, combining PEN with a specific exclusion diet [ 69 ]. The rationale of CDED is the avoidance of certain foods and dietary components (such as additives like emulsifiers or maltodextrins, food preservatives, etc), mostly belonging to western diets, deemed to act as triggers for intestinal inflammation, dysbiosis, altered intestinal mucous layer and impaired barrier function [ 12 , 21 , 22 , 70 , 71 ]. In addition, the use of real foods, even though in a controlled way, seems to meet the request of patients and their parents, often blaming the monotony of EEN as responsible for a low adherence to treatment [ 72 , 73 ].…”
Section: Nutritional Strategies In Induction Of Remission In Pediamentioning
confidence: 99%
“…Moreover, it seems that the use of elementary formulas with a low lipid content can be better tolerated by SMA1 children. In particular, all patients who have an abnormal gastric emptying can benefit from low-fat diet, which can help to improve motility and reflux [ 58 ]. Unfortunately, additional data are needed to confirm these benefits.…”
Section: Nutritional Aspects: Critical Issues and Possible Solutionsmentioning
confidence: 99%